PENGARUH PEMBIASAAN MEMBACA RATIB AL-HADDAD TERHADAP KEDISIPLINAN SANTRI - Roichatul Ismiyah; Siti Mutholingah (STAI Ma'had Aly Al-Hikam Malang, 2024)
Discipline is an attitude that shows a willingness to comply with and obey the provisions, rules and regulations that apply. To achieve life goals, especially in terms of worship and morals. Discipline will be formed by getting used to doing something good and doing it consistently and continuously. Therefore, instilling a disciplined attitude is very necessary for every educational institution. As-Sholchah Islamic Boarding School for Girls implements the habit of activities that are arranged in a fixed schedule and carried out consistently. The purpose of this study was to identify whether there is an influence of the habit of reading Ratib Al-Haddad on the discipline of students and to determine how much influence the habit of reading Ratib Al-Haddad has on the discipline of students. The type of research used is quantitative research. Hypothesis testing uses a simple linear regression test. The results of this study reveal the influence of the habit of reading Ratib Al-Haddad on discipline. The large influence of the habit of reading Ratib al-Haddad on the discipline of students at the As-Sholchah female Islamic boarding school based on simple linear regression analysis guided by R Square is 46%.